2017
DOI: 10.7575/aiac.alls.v.8n.3p.38
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing Listening and Speaking Activities of Iranian EFL Textbook Prospect 3 Through Bloom's Revised Taxonomy

Abstract: Some significant components are essential in teaching a language. Among these, textbooks are the most significant ones and must be considered seriously. Textbooks play an important role in EFL teaching and learning because they can provide ready-made materials to both teachers and students. Besides, if textbooks aren’t used appropriately, they may spoil the process of teaching. This study aimed at analyzing listening and speaking activities of the textbook Prospect 3 which is used for Junior High School third … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(25 citation statements)
references
References 4 publications
1
16
0
Order By: Relevance
“…Students master the ability to remember better than the ability to understand and analyze. This result is in line with the research Chalak & Mizbani about listening and speaking analysis which revealed that the ability to remember in listening activities was 60% [34]. The ability to remember in this study also occupies the largest percentage compared to other abilities.…”
Section: Discussion Of the Resultssupporting
confidence: 91%
“…Students master the ability to remember better than the ability to understand and analyze. This result is in line with the research Chalak & Mizbani about listening and speaking analysis which revealed that the ability to remember in listening activities was 60% [34]. The ability to remember in this study also occupies the largest percentage compared to other abilities.…”
Section: Discussion Of the Resultssupporting
confidence: 91%
“…This notion is corroborated by a study, for instance, which was conducted by Sobkowiak (2016) even though there was credence that a textbook could enhance the student's critical thinking ability, it was yet found to be limited in his study. Similarly, Mizbani and Chalak (2017) revealed that an EFL textbook investigated in their study was found to not accommodative in terms of higherorder thinking skills. Thereby, it should be taken into account that the textbook selection process is not a taken-for-granted process, there should have some considerations which could be hinged on the evaluation conducted.…”
Section: Introductionmentioning
confidence: 85%
“…What is more, T3 said that the students with low cognitive aspects will face difficulties in receiving the material because the language presented is all in English. Teachers sometimes do not found a necessary material based on K-13 so they should employ supplementary materials (Mizbani & Chalak, 2017). It is to increase students' ability to comprehend the concept (Susiati & Mufidati, 2020).…”
Section: The Teachers' Difficulties On Using the Bookmentioning
confidence: 99%